2016
DOI: 10.1177/1062860616644328
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Patient Safety Measures in Adult Primary Care

Abstract: Safety measure development has focused on inpatient care despite outpatient visits far outnumbering inpatient admissions. Some measures are clearly identified as outpatient safety measures when published, yet outcomes from quality improvement studies also may be useful measures. The authors conducted a systematic review of the literature to identify published articles detailing safety measures applicable to adult primary care. A total of 21 articles were identified, providing specifications for 182 safety meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…25 Collectively, these findings can inform how and what to start measuring patient safety performance in primary care, especially when the number of safety indicators specific to primary care remains limited compared with the inpatient measures. 42,43 The analytic classification of a personnel or patient perspective as nonnarrated does not sufficiently indicate that it is not considered important and/or an element of patient safety to them. This study sought to capture the meanings of patient safety that were most salient to the participants.…”
Section: Discussionmentioning
confidence: 99%
“…25 Collectively, these findings can inform how and what to start measuring patient safety performance in primary care, especially when the number of safety indicators specific to primary care remains limited compared with the inpatient measures. 42,43 The analytic classification of a personnel or patient perspective as nonnarrated does not sufficiently indicate that it is not considered important and/or an element of patient safety to them. This study sought to capture the meanings of patient safety that were most salient to the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors from different stakeholders and parties involved in healthcare interlock to be measured against one goal: patient outcome. Although the 1999 Institute of Medicine (IOM) report To Err Is Human (Kohn et al., 1999) has significantly accelerated the safety measure development, the systematic review on patient safety by Hatoun and colleagues (Hatoun et al., 2016) revealed that research has yet primarily focused on inpatient care. Nonetheless, ambulatory setting is actually where most medical care is administered and hence should play an increasingly important role regarding patient safety (Montano et al., 2016; Sockolow et al., 2017; Zonana et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nothing was discovered that was either commonplace or appropriately sophisticated. Similarly, Hatoun et al 48 undertook a systematic review of patient safety measures in adult primary care. They found 21 articles, including a total of 182 safety measures, and classified these into six dimensions: (1) medication management, (2) sentinel events, (3) care co-ordination, (4) procedures and treatment, (5) laboratory testing and monitoring and (6) facility structures/resources.…”
Section: Overall Performance Measurementmentioning
confidence: 99%